Estudo exploratório sobre o processo de contratação de serviços de empreitada e o seu impacto em obras de edificação - Adriana Guimaraes Duca (2015)
This paper aims to carry out an exploratory study on the process of hiring contracts services in the civil construction industry and its impact in the management of a housing project. The focus of the work is to establish general characteristics for a contract management process as well as the financial performance related to it, and an exploratory study of this practice in a major construction company. Literature points a market trend in replacing the workers for contract labor due to the easeof demobilization of the last during a financial crisis. It also points that the increase in subcontracting works creates management issues due to improper information flow between construction company and contractor. In the research development, a multiple case study was conducted for the analysis of three housing works of a construction company. Data on the overall process of hiring, management and characteristics that impact the financial results of each work were obtained by semi-structured interviews, direct observation of work routine and analysis ofcompany reports. It was noticed that the procurement process in the studied company follows the basic principles approached by the PMBOK. However, there are some suggestions not followed by the construction company which impact the financial result of the work. From the analysis of each construction work, the importance of a complete contract management was demonstrated, in which the manager has total control of all the information about the contract and its execution. Thereforeyou can prevent or mitigate negative impacts on the financial results of the construction work, and even point out unexpected positive impacts.